A research on the structural changes of supply networks for automotive parts. Issue 3 (4th November 2016) - Kim, Tae Hyun
Abstract : This research is to examine the influence of the supplier's network embeddedness for automotive parts. The research model was based on the network theory with social capital variables such as relational social capital, structural social capital and structural holes. An empirical analysis was fulfilled to investigate the effect of the buyer–supplier networks under different conditions. Independent variables employed for the study are relational and structural social capital and structural holes, and the dependent variable is the performance of suppliers measured by ROA (return on asset). Data were gained by Korea Auto Industries Cooperative Association (KAICA) to test the hypothesis of this research. Regression analysis was adopted to find relationships between the variables. The results of this study show that both relational and structural social capital have a positive impact on supplier's performance. Structural holes have positive influences on supplier performance as well. The interaction between relational social capital and the strong tie with an innovative buyer has a positive impact on supplier performance. The interaction between structural social capital and supplier interaction also has a positive impact on supplier performance.